The Toucher of Books: An Interview with Ninotchka Rosca - Militante, Clarissa V. (Likhaan: The Journal of Contemporary Philippine Literature, 2023)
Among the brightest literary lights of her generation, Ninotchka Rosca, now 75 and long based in New York, continues to draw attention and admiration for both her writing and her activism. The author of at least two celebrated novels, several collections of short stories, and books of nonfiction, Rosca looks back on a chldhood steeped in books and reading, on her literary influences, and on her many and continuing advocacies. This lively conversation with prizewinning novelist and literature professor Clarissa Militante was culled from a longer interview conducted over Zoom for the UPICW’s Akdang Buhay project in 2022.)